Jointly Optimized Design of Distributed Goppa Codes and Decoding - Feng, F. A.; Yang, F. F.; Chen, C.; Zhao, C. L. (Radioengineering, 2023)
In order to improve the adverse influence of fading channel in communication system, a distributed Goppa coding scheme is proposed in this paper. Two Goppa codes are set at the source node and the relay node in this scheme respectively. An optimal design criterion at the relay is proposed to obtain the optimal joint resultant code at the destination. Furthermore, two novel joint decoding algorithms are proposed to enhance the overall BER performance of the proposed scheme. Monte Carlo simulations show that the proposed distributed Goppa coding scheme outperforms the non-cooperative scheme. Moreover, the proper information selection approach at the relay performs better than random selection in the proposed distributed Goppa coding scheme.